Injury mechanism classification in soccer videos - Murthy,O. V. R.; Goecke, R. (IEEE International Conference on Computer Vision (ICCV) Workshops, 2015, Santiago, 2015)
Soccer is a very popular sport but also has a high rate of injuries. In this paper, player falling events in soccer videos are classified into five major categories. These categories have been identified by soccer coaches as the major mechanisms behind player injuries. Automatic detection of these events will be useful to coaches to plan specific training modules and to impart individual training to the players that will enhance their physical strength and also their playing style. A Bag-of-Words framework is used and a baseline classification accuracy is established that will serve as a reference point for further work.